Porositas Dan Sorptivity Beton OPC Dan Beton OPC POFA Dengan Perbaikan Air Gambut Sebagai Air Pencampur Menggunakan Kapur Tohor Di Lingkungan Gambut - Sormin, Lina S; Olivia, Monita; Syaputra, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The use of peat water is often used as concrete mixing water in areas difficult to obtain clean water. Peat water containing a low pH is not recommended as concrete mixing water because it can reduce the quality of concrete. Mineral materials such as Palm Oil Fuel Ash (POFA) used in the concrete mix to increase the density of the resulting. This study aims to assess the physical properties such as porosity and water sorptivity concrete using peat as concrete mixing water. Type of cement used in the concrete mixture is OPC and OPC POFA 10%. Peat water for the research came from Rimbo Panjang, Kampar, Riau and POFA derived from Perhentian Raja, Kampar, Riau. Research results show that concrete repair using quicklime 40 milligrams for peat water soaked peat environment has a high porosity and sorptivity.Keywords: OPC, Palm Oil Fuel Ash (POFA), peat water, quicklime